The study of functional asymmetry in students and schoolchildren practicing martial arts - Vyacheslav V. Romanenko; Olha O. Podrihalo; Leonid V. Podrigalo; Sergii S. Iermakov; Zhanna V. Sotnikova-Meleshkina; Oksana V. Bobrova (Physical Education of Students)
Background and Study Aim. The study of functional asymmetry in students and schoolchildren practicing martial arts using a computer test.